Peer Collaboration: A Model to Support Counsellor Self-Care - Barlow, Constance A.; Phelan, Anne M. (Canadian Journal of Counselling and Psychotherapy, 2007)
In the context of a larger case study on how continuous learning in the workplace could be achieved through the implementation of peer collaboration, the process of how counsellors engaged in self-care within a large health care organization became clearer. This article isbased on data derived from a qualitative analysis of nine transcribed audiotaped meetings of the Counselling Trio, a group of three grief counsellors in a large urban health region. By describing the formation of the peer collaboration groups, the processes that led to the Counselling Trio’s successful collaboration, and the impact of the experience on the three participants, we attempt to illustrate how peer collaboration can be used as a forum for self-care among grief counsellors. We conclude with a critical reflection on the potentialof peer collaboration as a vehicle for organizational support of counsellor self-care.